Comparison of corneal endothelial cell loss during phacoemulsification using continuous anterior chamber infusion versus those using ophthalmic viscosurgical device: Randomized controlled trial - Nayak B; Jain Elesh (Indian Journal of Ophthalmology, 2009)
Aim: We conducted this study to evaluate and compare corneal endothelial cell loss between phacoemulsification with continuous anterior chamber infusion using anterior chamber maintainer (ACM) and phacoemulsification using ophthalmic viscosurgical device (OVD). Materials and Methods: This was a prospective, randomized controlled trial. Fifty eyes of 47 patients of senile cataract undergoing phacoemulsification were included. Patients were randomly allocated into two groups of 25 eyes each. Cataract surgery was performed by phacoemulsification with anterior chamber (AC) continuous infusion with balanced salt solution (BSS) plus and ACM without OVD in Group A, and in Group B, phacoemulsification was performed using OVD with BSS plus. Corneal endothelial cell count and pachymetry were performed preoperatively and postoperatively on day 1, day 7, and day 30. Results: The mean increase in pachymetry was 4.86%, 2.94%, and 1.94%, (Group A) and 5.95%, 3.94%, and 0.51%, (Group B) on first, seventh, and 30 th postoperative day respectively. The difference between the percentage increase in pachymetry between the two groups was not significant at day 1 ( P = 0.441), day 7 ( P = 0.298), and day 30 ( P =0.174) postoperatively. The density of endothelial cells decreased postoperatively (day 30) by 7.38% (Group A) and 7.47% (Group B) without any significant statistical difference ( P = 0.983) between two groups. Conclusion: Use of ACM for continuous AC infusion and omission of OVD during phacoemulsification did not cause significant difference in corneal swelling or endothelial cell loss in the immediate postoperative period up to one month.